Mechanisms of Action of Non-Steroidal Anti-Inflammatory Drugs for the Prevention of Alzheimer's Disease - Cole, Greg M.; Frautschy, Sally A. (CNS & Neurological Disorders - Drug Targets, 2010)
Alzheimer's disease (AD) is accompanied by an activation of the innate immune system, and many epidemiological studies have shown reduced risk for dementia or AD associated with chronic consumption of non-steroidal anti-inflammatory drugs (NSAIDS). These observations led to animal model studies to test the hypothesis that NSAIDs can be disease-modifying for some aspects of AD pathogenesis. NSAIDS cannot only suppress inflammatory targets, which could contribute to neuroprotection, they also slow amyloid deposition by mechanisms that remain unclear. Several large clinical trials with NSAID therapies with AD subjects have failed, and cyclooxygenase-2 does not appear to be a useful target for disease modifying therapy. However, there may be apolipoprotein E E4 pharmacogenomic effects and a real but delayed positive signal in a large primary prevention trial with naproxen. This encourages researchers to re-address possible mechanisms for a stage-dependent NSAID efficacy, the subject of this review.
Keywords: non-steroidal anti-inflammatory drugs